TI_GERICHTE 35.2020.95 vom 26. Mai 2021 , Discussa eziologia disturbi alla coscia sx e diritto a una rendita d'invalidità - TI Tribunale d'appello (2021)
Discussa eziologia disturbi alla coscia sx e diritto a una rendita d'invalidità